Inter-governmental managerial mechanisms in Australia - Dai Yagihara (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
This paper looks at the intergovernmental mechanisms by which federalism operates in Australia, notably the Council of Australian Governments (COAG), Commonwealth Grants Commission (CGC), Australian Loan Council (ALC). These three main systems contribute to improve Australian intergovernmental relations, that is, establish managerial mechanism in Australia. Australia's intergovernmental system provides the foundation for new federalism operations. And these mechanisms are an opportunity to consider the intergovernmental relations as a whole. Reform of intergovernmental operations and federal financial arrangements would contribute to greater economic efficiency, improved equity outcomes, and greater accountability and transparency. Reform will deliver benefits to the national economy and improve both Commonwealth and state fiscal operation.
Keywords: H71; H74; H77; 330; Australian Loan Council; Intergovernmental fiscal relations of Australia; the Commonwealth Grants Commission; Debts; Public Australia; the Council of Australian Governments